Xử lý số liệu GLONASS phục vụ nghiên cứu địa động lực - Hải, Vy Quốc (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Processing GLONASS data for geodynamics study The application of two (or more) global positioning systems offers many practical benefits. In recent times, outside the GPS, GLONASS system was developed, to meet the surveying, navigation requirements, so the GLONASS data processing has become necessary. In this paper, some GLONASS data of IGS sites have been processed by Bernese software. The processing results achieved satisfactory accuracy with relative errors of approximately 1:50 000 000. This success set the stage for the application of the systems (GLONASS system and the immediate future Galileo) for works in large spatial scale with high accuracy